Do persons with intellectual and developmental disabilities prefer to save the best for last in an MSWO? A preliminary investigation. (25th April 2022) - Castillo, Mariana I.; Frank‐Crawford, Michelle A.; Liesfeld, Jody E.; Doan, Trang M.; Newcomb, Eli T.; Rooker, Griffin W.; Borrero, John C.
Abstract: The multiple stimulus without replacement (MSWO) preference assessment is commonly used to identify potential reinforcers. In this arrangement, individuals can choose the order in which they consume edibles or activities. The item selected first is often designated the highest preferred, and the item selected last is often designated the least preferred. Scattered reports suggest that some individuals may save the best for last in an MSWO. Despite these reports, few systematic evaluations of "saving the best for last" in the MSWO have been conducted. We examined this phenomenon using an MSWO and progressive‐ratio‐reinforcer assessment. Evidence of "saving the best for last" was obtained for one of four individuals across assessments involving edibles and leisure activities, respectively.